New types of tourism and tourism marketing in the post-industrial world - Árva , László; Deli-Gray, Zsuzsa (Applied Studies in Agribusiness and Commerce, 2010)
At the end of the 20th century in the most developed countries economy and society went through profound transformation. The emerging post-industrial society can be characterised by the dominance of service industry, more leisure time of the population, higher disposable income and more conscious consumers. These conscious consumers are more and more quality orientated and reject undifferentiated mass products. New customers of tourism and hospitality industry are not only more affluent – so less price conscious – and more quality orientated but they are also seeking activity, participation, fantasy, and experience. These new types of tourists are interested rather in aesthetic aspects of life and are seeking highly differentiated, personalised experience. In the following article the authors, professors of the French ESSCA business school overview theoretical aspects of new, post-Fordist tourism demand and present examples of the new tourism and hospitality products having emerged in the developed countries during the last years.